New York to Dallas - Robb, J. D., 1950- (Robb, J. D., 1950- In death novel., 2011)
When a monster named Isaac McQueen, taken down by homicide cop Eve Dallas back in her uniform days, escapes from Rikers Island, he has two things in mind. One is to pick up where he left off, abducting young victims and leaving them scarred in both mind and body. The other is to get revenge on the woman who stopped him all those years ago.